THE DIFFERENCES IN SOME ANTHROPOMETRIC CHARACTERISTICS BETWEEN TOP FOOTBALL PLAYERS AND RECREATIONAL PLAYERS - Stevo Popović,; Molnar Slavko,; Bojan Mašanović, (Sport Scientific And Practical Aspects, 2025)
This research was aimed at gaining relevant knowledge about important differences with respect to some anthropometric characteristics of the best football players and their peers who play football on a recreational basis. The sample included 56 respondents, aged 28 (±1 year) divided into two subsample groups. The first subsample group was comprised of 26 respondents who practice football at a Football Club “Vojvodina” from Novi Sad, while the other subsample included 30 respondents who play football recreationally. The sample of variables contained 20 anthropometric measures that defined longitudinal and transversal dimensionality of the skeleton, then the body mass and body volume as well as the subcutaneous adipose tissue. The results of the measuring were analyzed by means of a statistical procedure labeled a significance test of two arithmetic means conducted on independent samples or popularly known a t-test. Based on the results it was concluded that significant differences occur in the case of all the variables used to assess the subcutaneous adipose tissue, as well as in the case of most variables for assessing the body mass and body volume at a significance level of p=.05.